The relationships among self‐regulation, emotional intelligence, willingness to communicate, and reading comprehension of Persian foreign language learners: Structural equation modeling - Taherkhani, Reza; Moradi, Reza (Foreign language annals, 2022)
This nationwide mixed methods study investigated the relationships among self‐regulation (S‐R), emotional intelligence (EI), willingness to communicate (WTC), and reading comprehension ability of Persian foreign language (PFL) learners in Iran. Therefore, 141 non‐Persian students, from 28 different countries studying at 12 universities across Iran were selected to participate in the study. The participants were asked to answer S‐R, EI, WTC scales, and a reading comprehension test. To deeper understand the constructs in the questionnaires and to triangulate the data, structured interviews were conducted with 45 participants. Besides, for checking the strengths of the causal relationships among the variables, structural equation modeling was utilized. The three independent variables were strong predictors of reading comprehension, with WTC being the strongest predictor. Considering the increasing number of PFL learners, implications focus on how second language practitioners, especially those concerned with PFL can benefit from the results of this study. The Challenge The role of individual differences in the process of language learning, particularly in reading comprehension, has been recognized as very influential. No research has been conducted to explore the possible effects of S‐R, EI, and WTC on Persian foreign language (PFL) learners' reading comprehension ability. Can S‐R, EI, and WTC predict PFL learners' reading comprehension ability? What is a valid model of interrelationships among S‐R, EI, WTC, and reading comprehension? By answering these questions, this nationwide mixed methods study tries to fill the gap in the literature.